Tourism and political change - Butler, Richard; Suntikul, Wantanee (Oxford : Goodfellow Publishers Ltd., 2017)
Tourism is a vital tool for political and economic change. With international contributions from experienced individuals, this book cover general themes and issues, with three thematic sections with original chapters, and a concluding section. It covers a variety of international political changes at different scales and their resulting effects.
Part One: Changes in political relationships -- Part Two: Increasing autonomy -- Part Three: Normalisation and opening -- Part Four: Uncertain future.
Includes bibliographical references and index.
Keywords: TOURISM -- POLITICAL ASPECTS